2014
DOI: 10.1148/radiol.13122661
|View full text |Cite
|
Sign up to set email alerts
|

How to Perform Parathyroid 4D CT: Tips and Traps for Technique and Interpretation

Abstract: Parathyroid four-dimensional (4D) computed tomography (CT) is an imaging technique for preoperative localization of parathyroid adenomas that involves multidetector CT image acquisition during two or more contrast enhancement phases. Four-dimensional CT offers an alternative or additional tool in the evaluation of primary hyperparathyroidism. The purpose of this article is to describe the 4D CT technique and provide a practical guide to the radiologist for imaging interpretation. The article will discuss the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
113
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 31 publications
3
113
0
8
Order By: Relevance
“…However, in studies related to parathyroid adenoma localization, it has been reported that majority of cases originate in the inferior glands (30). Of the patients for whom complete data were available, it was observed that WCCA behaved like adenoma rather than WCCH with respect to localization.…”
Section: Discussionmentioning
confidence: 96%
“…However, in studies related to parathyroid adenoma localization, it has been reported that majority of cases originate in the inferior glands (30). Of the patients for whom complete data were available, it was observed that WCCA behaved like adenoma rather than WCCH with respect to localization.…”
Section: Discussionmentioning
confidence: 96%
“…[5][6][7] In the past decade, multiphase CT has emerged as an additional technique for adenoma localization. 1,2,[8][9][10][11][12][13][14] In addition to lesion identification, CT allows precise localization based on welldefined anatomic landmarks. Following its introduction, multiphase CT was referred to as 4D-CT. 9 The term "4D" referred to the 3 dimensions provided by the CT scan with the added dimen-sion of time due to the functional information offered by the multiple phases of imaging.…”
mentioning
confidence: 99%
“…1 The characteristic features of parathyroid adenomas on 4D CT are low attenuation on noncontrast imaging, peak enhancement on the arterial phase, and washout of contrast on the venous phase. [2][3][4] These allow differentiation between a parathyroid adenoma and its mimics, such as thyroid nodules and lymph nodes.…”
mentioning
confidence: 99%
“…5,6 Small arteries cannot be seen on nuclear scintigraphy or MR imaging because of lower spatial resolution, and they have not been described on single venous phase CT, to our knowledge. In a recent review article, the authors noted the presence of a "polar vessel" sign on the arterial phase of 4D CT. 4 The polar vessel sign can represent either an enlarged feeding artery or a draining vein seen on the arterial phase of imaging, and it is characterized by a vessel that terminates in a parathyroid adenoma and that is larger than contralateral neck vessels in a similar location.…”
mentioning
confidence: 99%